Sustainable Development of Traditional Houseboat: Based on the Research of Primitive Architecture of Li Nationality in Hainan Province - Yang, Fuyu (European Journal of Sustainable Development, 2018)
Li Nationality is the earliest boong in Hainan Province, their history and cultures are listed in The World’s and National Intangible cultural Heritage. Li Nationality’s dwellings space and model have their peculiar vantages including the ancient wisdom of sustainable environmental protection and respecting natural world. Li Nationality adopted the idea of building a boat to construct houses and organized their own families before 4000 years ago and the houseboats contained typical characteristics of simple, saving materials and making good use of the old boats . However, with the modern cultures influence of Han Nationality, more Li people is giving up their traditional houseboats. The only reserved village which possesses traditional houseboats is Baizha in the Dongfang City of Hainan Province. Hainan Province government and researchers are trying to protect the related cultures and houseboats style architecture by moving them into the scenic area or introduce more tourists to visit village having houseboats to increase the income of Li Nationality and make them adapt themselves to modern economic society based on reserve traditional life-style. Step 1 is digging historical and cultural information in Li Nationality, their fairy stories, religious faith and folk songs, step 2 is applying all those materials to intangible cultural heritage list and getting enough subsidiary funds from governments, step 3 is organizing researchers and architects to visit village, step 4 is attracting more tourists to visit it, reserving this traditional architecture style based on cyclic economy. Keywords: sustainable development, houseboats, Li Nationality